Gender and educational inspectorate. A study on the case of Aragon - Lozano García, Alejandro (Avances en Supervisión Educativa, 2023)
The first section reviews the state of the art on gender and educational inspectorate and gender equality policies in the context of the Autonomous Community of Aragon, and describes the pragmatic methodological approach used to study, in a second section, the evolutionary data from 2009/2010 to 2023 on the presence of women in this type of positions, not only in terms of numbers, but also in terms of access to and distribution of positions of responsibility. A third section analyses the answers given by female and male inspectors to a questionnaire that seeks to investigate the family, personal, motivational or professional constraints and facilities that women encounter in accessing and remaining in the inspection profession. The general conclusion is that a positive evolution is taking place in terms of the incorporation of women in the Education Inspectorate, although there are still more or less tacit aspects that indicate that full equality may not yet have been achieved.